The Tshezi of the Transkei: an ethnographic study - Holt, Basil (My University, 2015)
No abstract
A Thesis presented for the Degree of Doctor of Philosophy in the University of the Witwatersrand, Johannesburg. December 1969,
Keywords: Tshezi (African people); Ethnology--South Africa--Transkei; Education--Aims and objectives--South Africa